Microgrid Communication and Security: State-Of-The-Art and Future Directions - Farah Aqilah Bohani; Sitti Rachmawati Yahya; Siti Norul Huda Sheikh Abdullah (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2021)
The microgrid communication network with proper connectivity among microgrid resources is play important role to maintain a stability and reliability of the microgrid. Application of suitable communication network and protocol and highlighted the best security measurement is one of the elements to achieve those broad objectives. The communication network and protocol that has been implemented in existing microgrid has different types and objective which is depend on specific application. To secure the communication network and protocol, many security approaches is proposed. In this paper, a review of microgrid communication and its security is shown and future direction of communication network and protocol with its security also provided.